Analysis of Language Style in the Poetry "Saaqulu Laki: Uhibbuki" by Nizar Qabbani - Muhammad Nazar; Febrianisa, Sindy (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
In literary works, every author is free to express the results of his thoughts. Likewise, Nizar Qabbani, in his literary work entitled "Saaquluu Laki Uhibbuki" has his own language style to tell the story of my feelings which were mixed together when he was writing this poem. And tell about the process of selecting the best sentences from the best sentences to write in this poem. Therefore, a stylistic study is needed, looking at the linguistic forms used by Nizar Qabbani in order to understand the meaning of the poem. The method used in this analysis is descriptive qualitative, then continued with data collection methods in the form of listening methods with basic techniques in the form of tapping techniques, then continued with free-involved listening techniques, proficient and note-taking. The results of this research show that the author uses several language styles according to Syihabb Qalyubi's perspective. The research results include, first, the phonological aspect of emphasizing the vowel "i" in each stanza in the poem. Second, the morphological aspect contains repetition of sentences as well as fi'il madhi, mudhori' and amr which have their own influence on the poetry. Third, the syntactic aspect is the sentences taqdhim and ta'khir, kalam khobar and insha'. Fourth, the imargery aspect which contains majaz mursal, majaz kinayah, tasybih mua'kad, tasbih mursal, majaz isti'arah, isti'arah makniyyah in his poetry.